Succession in Family Business: A Case study of Chowkaset 2003 Part., Ltd - Tuntrabundit, Pranot; Zhang, Fan; Nadeau, Benoit (KKBS Journal of Business Administration and Accountancy, 2018)
The main purpose of this case study was to investigate succession characteristics and process in a family business with effective transition. Understanding this challenging transition, more insights into methods for successful transitions and for sustainable business after the succession. The selected case study was a poultry farm in Thailand. The results of the study revealed that the succession process in this family business began at the selection of the potential successor who had been trained for management knowledge and skills. During the transition process, the successor was empowered by allocating clear authority on management. The previous executive played roles as a consultant and shadow executive, who took part in decision making on important issues that may impact the business. The findings of this study clearly show that systematic succession planning impacts sustainable family business. These findings will be useful to other family businesses by adopting this succession planning in their family businesses for survival and sustainable businesses.